2008
DOI: 10.3354/ab00079
|View full text |Cite
|
Sign up to set email alerts
|

Wave surge increases rates of growth and nutrient uptake in the green seaweed Ulva pertusa maintained at low bulk flow velocities

Abstract: Effects of wave surge on growth and nutrient uptake in the green seaweed Ulva pertusa were measured in small tanks fed natural seawater via a dump bucket that could be either locked in place to deliver water continuously, or set to tip at particular volumes. Rates of bulk water flow through the tanks were low (<13 mm s -1 ), as may be typical of highly sheltered marine and estuarine environments. At the maximum bulk flow rates tested, wave surge increased growth in wet mass 1.6-fold. Wave surge increased the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…But at nearby shores moderately exposed to waves, grazers have no measurable effect on algal biomass and shading rock substrates from direct solar radiation can have positive effects on some years, but not on others. Because the development of ephemeral algae is often limited by nutrient flux (Barr et al, 2008;Wheeler, 1980), and because nitrate supply in the SCC is remarkably low, we submit that differences in macroalgal production across wave exposure and between years can be partly explained by small variation in nutrient fluxes. Other processes, such as interannual differences in propagule supply and selective herbivory could have also played an important role .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But at nearby shores moderately exposed to waves, grazers have no measurable effect on algal biomass and shading rock substrates from direct solar radiation can have positive effects on some years, but not on others. Because the development of ephemeral algae is often limited by nutrient flux (Barr et al, 2008;Wheeler, 1980), and because nitrate supply in the SCC is remarkably low, we submit that differences in macroalgal production across wave exposure and between years can be partly explained by small variation in nutrient fluxes. Other processes, such as interannual differences in propagule supply and selective herbivory could have also played an important role .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing desiccation stress through water splash (Kaehler and Williams, 1998), wave exposure can enhance benthic primary productivity because it facilitates nutrient uptake by increasing effective submersion times, especially in microtidal regions, and by decreasing the thickness of the boundary layer on the surface of algal tissues (Barr et al, 2008;Hepburn et al, 2007;Wheeler, 1980). In this study, we characterized the extent of seasonal blooming of mid shore ephemeral algae, and experimentally measured the effects of herbivory and amelioration of environmental stress (shading) on algal biomass under varying wave exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The balance between input and output is the tissue phosphorus content. Two major determinants of the rate of input are the maximum rate of phosphate uptake and the concentration of phosphate in the surround- ing seawater, though other factors such as water motion (Barr et al 2008) will also affect rates of acquisition. The major determinant of demand is likely to be growth rate, but it will include any other process that increases the demand for phosphorus.…”
Section: Ulva Intestinalismentioning
confidence: 99%
“…Seaweeds for uptake experiments were collected within 48 h prior to use and kept in a large (1.3 m 3 ) outdoor holding tank with regular seawater (from the same location as where the seaweeds were collected) flow, turbulence and mixing (input water was via a dumping system of about 10 l every 2 min) (Barr et al 2008). Trials comparing algae that were maintained in this system for 48 h and freshly collected seaweed showed no significant difference in phosphate uptake rate (authors' unpubl.…”
Section: Phosphate Uptakementioning
confidence: 99%
“…Growth has been shown to increase with increased velocity in artificial stream systems, and investigations of periphyton growth has suggested that there is a critical flow velocity at which the growth and chlorophyll-a content is maximized (Labiod et al, 2007;Barr et al, 2008;Carpenter et al, 1991;Cronk and Mitsch, 1994). Potential explanations for this phenomenon include altered light regimes and the breakdown of diffusion boundary layers resulting from higher levels of turbulence (Grobbelaar, 2009;Dodds and Biggs, 2002;Blersch et al, 2013).…”
Section: Introductionmentioning
confidence: 96%